Analisis Iman Yang Hidup Dalam Kekristenan Berdasarkan Yakobus 2:17-20 - Djone Georges Nicolas; Adolf Bastian Butarbutar; Rosianna Purba; Siesta Napitupulu; Vroly Ruth Wowor (Jurnal Multidisiplin Madani, 2022)
The purpose and focus of this research are to analyze the living faith in Christianity based on James 2:17-20. As an approach, the author uses descriptive qualitative methods and exegesis and collects data through the Bible, various journals and books, and documents that discuss and relate to the topic of discussion. For example, confession of faith in Christ, which is limited only to the words that come out of one's mouth, often becomes a stumbling block because it is not appropriate or different from the deeds it shows. As a result, the believer's faith in Christianity is a living faith: faith that is evidenced through acts of obedience to the commandments of God which are believed. In conclusion, if the faith professed by believers is active, the world can certainly see it, not only by hearing about the believers' confession of faith but also will prove it through the lives of believers who practice the word of God that they believe in and want to enjoy. Because something that is alive or has life must have characteristics that can witness its life, as well as faith